Discovery of nitrogen-responsive microbial indicators as metrics of freshwater ecosystem health - Jonathan Warren; Caitlin de Vries; Laura H. Hunt; Amy C. Thorpe; Susheel Bhanu Busi; Martyn G. Kelly; Dina-Leigh Simons; Joe D. Taylor; Daniel S. Read; Kerry Walsh (Water Research, 2026)

River Microbiomes as Sentinels of National‐Scale Freshwater Ecosystems - Amy C. Thorpe; Susheel Bhanu Busi; Jonathan Warren; Lindsay K. Newbold; Joe D. Taylor; Kerry Walsh; Daniel S. Read (Global Change Biology, 2026)
Freshwaters face increasing pressures from chemical, hydrological and climatic changes, yet tools for assessing their condition remain limited. River biofilms, composed of diverse microbial communities, integrate environmental signals over space and time, making them sensitive indicators of river health. Using 16S rRNA gene sequencing of more than 1600 biofilms collected across a national river network, we quantified bacterial diversity and community composition and applied network analysis to identify ecologically cohesive sub‐communities with keystone taxa underpinning community stability. Alkalinity, dissolved oxygen, nitrate‐nitrogen and temperature were among the principal gradients shaping community composition. Threshold indicator analyses identified taxa with breakpoints along these gradients, revealing interpretable ecological thresholds. Our results demonstrate the potential for microbiome‐based monitoring frameworks that could complement existing biotic indices, enabling early detection of ecological changes and supporting the integration of genomic indicators into routine ecosystem assessment. This scalable approach offers a powerful strategy for managing freshwaters under accelerating anthropogenic pressures.

What controls current and future background vulnerability of rivers to eutrophication and pathogens? - Michael Hutchins; Emma Gardner; Lisa Gechelle; Andrew Johnson; Yueming Qu; Dinara Sadykova; Michael Bowes; Daniel Read; Claire Robertson (Journal of Hydrology, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

Evaluation of an open-source nutrient delivery model for estimating pesticide loads in river catchments - Emily V. Upcott; Virginie Keller; Daniel S. Read; Clarissa Rizzo; Jude Jeans; John W. Redhead (Science of The Total Environment, 2025)

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Effective Engagement Techniques Across the Agricultural Conservation Practice Adoption Process - Daniel J. Read; Erika Blair; Lisa Wainger (Environmental Management, 2024)

Dissemination and persistence of antimicrobial resistance (AMR) along the wastewater-river continuum - Daniel S. Read; H. Soon Gweon; Michael J. Bowes; Muna F. Anjum; Derrick W. Crook; Kevin K. Chau; Liam P. Shaw; Alasdair Hubbard; Manal AbuOun; Holly J. Tipper; Sarah J. Hoosdally; Mark J. Bailey; et al. (Water Research, 2024)

Do storm overflows influence AMR in the environment and is this relevant to human health? A UK perspective on a global issue - Holly J. Tipper; Isobel C. Stanton; Rachel A. Payne; Daniel S. Read; Andrew C. Singer (Water Research, 2024)

Achieving transformational change through the consilience of behavioral science and radical alternatives - Daniel J. Read; Matthew J. Selinske (Sustainability Science, 2024)
The integration of behavioral science into conservation science and climate science has enabled the development of both novel research questions and practical interventions. However, most behavioral interventions aim to change private, individual behaviors, rather than transform the political economic systems that drive current biodiversity, climate, and social crises. In this paper, we argue that closer collaboration between behavioral scientists working on biodiversity and climate issues, on the one hand, and advocates for radical alternatives to current political economic systems, on the other, could advance such needed systemic transformation. While the work of both groups is subject to some critique, we suggest that closer collaboration could enable the strengths of each to address the others’ weaknesses. This complementarity is particularly true when behavioral interventions are co-designed with advocates and targeted towards powerful individuals whose behavior could affect systems-level transformation. We use the fossil fuel divestment movement as an illustrative example of one way in which this collaboration could be mutually beneficial, and then outline potential political, practical, and ethical implications that may accompany such collaborations in the biodiversity conservation and climate change fields.

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Predicting river phytoplankton blooms and community succession using ecological niche modeling - Michael J. Bowes; Michael G. Hutchins; David J. E. Nicholls; Linda K. Armstrong; Peter M. Scarlett; Monika D. Jürgens; Nuria Bachiller‐Jareno; Isabelle Fournier; Daniel S. Read (Limnology and Oceanography, 2024)
Excessive phytoplankton concentrations in rivers can result in the loss of plant and invertebrate communities, and threaten drinking water supplies. Whilst the physicochemical controls on algal blooms have been identified previously, how these factors combine to control the initiation, size, and cessation of blooms in rivers is not well understood. We applied flow cytometry to quantify diatom, chlorophyte, and cyanobacterial group abundances in the River Thames (UK) at weekly intervals from 2011 to 2022, alongside physicochemical data. A niche modeling approach was used to identify thresholds in water temperature, flow, solar radiation, and soluble reactive phosphorus (SRP) concentrations required to produce periods of phytoplankton growth, with blooms only occurring when all thresholds were met. The thresholds derived from the 2011 to 2018 dataset were applied to a test data set (2019–2022), which predicted the timing and duration of blooms at accuracies of > 80%. Diatoms and nano‐chlorophyte blooms were initiated by flow and water temperature, and usually terminated due to temperature and flow going out of the threshold range, or SRP and Si becoming limiting. Cyanobacterial bloom dynamics were primarily controlled by water temperature and solar radiation. This simple methodology provides a key understanding of phytoplankton community succession and inter‐annual variation and can be applied to any river with similar water quality and phytoplankton data. It provides early warnings of algal and cyanobacterial bloom timings, which support future catchment management decisions to safeguard water resources, and provides a basis for modeling changing phytoplankton bloom risk due to future climate change.

Fate and behaviour of Microplastics (> 25µm) within the water distribution network, from water treatment works to service reservoirs and customer taps - Gbotemi A. Adediran; Ruairidh Cox; Monika D. Jürgens; Elise Morel; Richard Cross; Heather Carter; M. Glória Pereira; Daniel S. Read; Andrew C. Johnson (Water Research, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Benchtop x-ray fluorescence to quantify elemental content in nails non-destructively - Aaron J. Specht; Kolawole E. Adesina; Daniel E. Read; Marc G. Weisskopf (Science of The Total Environment, 2024)

Maximising environmental pressure-response relationship signals from diatom-based metabarcoding in rivers - Martyn G. Kelly; David G. Mann; Joe D. Taylor; Stephen Juggins; Kerry Walsh; Jo-Anne Pitt; Daniel S. Read (Science of The Total Environment, 2024)

Water-soluble polymers: Emerging contaminants detected, separated and quantified by a novel GPC/MALDI-TOF method - Eve C. Tarring; Isabelle Durance; Michael J. Harbottle; Robert Lucas; Daniel S. Read; Benjamin D. Ward (Environmental Pollution, 2024)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Assessing intervention effectiveness at promoting voluntary conservation practice adoption in agrienvironments - Daniel J. Read; Lisa Wainger (Conservation Biology, 2023)
Although implementing conservation practices on private farms and forests can produce substantial environmental benefits, these practices are not being adopted widely enough to result in measurable improvements at regional scales. Researchers have investigated the production and program factors influencing producer choices to voluntarily adopt these practices. However, the findings of reviews are inconsistent, raising questions about review methods, including the omission of relevant variables. Further, applying lessons from past work to promote adoption is difficult because many reviews investigated dispositional or demographic variables that practitioners and policy makers cannot directly observe or influence. We conducted a new review of 146 empirical studies that tested the effects of different interventions (e.g., financial incentives, outreach events, and nudges) on increasing the likelihood of producers adopting conservation practices. We conducted a metaregression of quantitative studies from diverse disciplines that filtered studies by quality (i.e., use of randomization and clear analysis reporting). We synthesized these results with a thematic analysis of qualitative studies on producer perspectives about conservation practices. Financial incentives had the strongest evidence of increasing producers’ likelihood of adopting conservation practices (odds ratio 1.86, p p

Gut and faecal bacterial community of the terrestrial isopod Porcellionides pruinosus: potential use for monitoring exposure scenarios - Jacinta M. M. Oliveira; Isabel Henriques; Daniel S. Read; Hyun S. Gweon; Rui G. Morgado; Sara Peixoto; António Correia; Amadeu M. V. M. Soares; Susana Loureiro (Ecotoxicology, 2021)

Assessing the impact of the threatened crucian carp ( Carassius carassius ) on pond invertebrate diversity: A comparison of conventional and molecular tools - Lynsey R. Harper; Lori Lawson Handley; Carl D. Sayer; Daniel S. Read; Marco Benucci; Rosetta C. Blackman; Matthew J. Hill; Bernd Hänfling (Molecular Ecology, 2021)
Fishes stocked for recreation and angling can damage freshwater habitats and negatively impact biodiversity. The pond‐associated crucian carp ( Carassius carassius ) is rare across Europe and is stocked for conservation management in England, but its impacts on pond biota are understudied. Freshwater invertebrates contribute substantially to aquatic biodiversity, encompassing many rare and endemic species, but their small size and high abundance complicate their assessment. Practitioners have employed sweep‐netting and kick‐sampling with microscopy (morphotaxonomy), but specimen size/quality and experience can bias identification. DNA and environmental DNA (eDNA) metabarcoding offer alternative means of invertebrate assessment. We compared invertebrate diversity in ponds ( N = 18) with and without crucian carp using morphotaxonomic identification, DNA metabarcoding and eDNA metabarcoding. Five 2 L water samples and 3 min sweep‐net samples were collected at each pond. Inventories produced by morphotaxonomic identification of netted samples, DNA metabarcoding of bulk tissue samples and eDNA metabarcoding of water samples were compared. Alpha diversity was greatest with DNA or eDNA metabarcoding, depending on whether standard or unbiased methods were considered. DNA metabarcoding reflected morphotaxonomic identification, whereas eDNA metabarcoding produced markedly different communities. These complementary tools should be combined for comprehensive invertebrate assessment. Crucian carp presence minimally reduced alpha diversity in ponds, but positively influenced beta diversity through taxon turnover (i.e., ponds with crucian carp contained different invertebrates to fishless ponds). Crucian carp presence contributes to landscape‐scale invertebrate diversity, supporting continued conservation management in England. Our results show that molecular tools can enhance freshwater invertebrate assessment and facilitate development of more accurate and ecologically effective pond management strategies.

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

The role of rhizofiltration and allelopathy on the removal of cyanobacteria in a continuous flow system - Ana Teresa Castro-Castellon; Jocelyne Mary Rose Hughes; Daniel Steven Read; Yaldah Azimi; Michael James Chipps; Nicholas Peter Hankins (Environmental Science and Pollution Research, 2021)

Contrasting community assembly processes structure lotic bacteria metacommunities along the river continuum - Hyun S. Gweon; Michael J. Bowes; Heather L. Moorhouse; Anna E. Oliver; Mark J. Bailey; Michael C. Acreman; Daniel S. Read (Environmental Microbiology, 2021)
Summary The heterogeneous nature of lotic habitats plays an important role in the complex ecological and evolutionary processes that structure the microbial communities within them. Due to such complexity, our understanding of lotic microbial ecology still lacks conceptual frameworks for the ecological processes that shape these communities. We explored how bacterial community composition and underlying ecological assembly processes differ between lotic habitats by examining community composition and inferring community assembly processes across four major habitat types (free‐living, particle‐associated, biofilm on benthic stones and rocks, and sediment). This was conducted at 12 river sites from headwater streams to the main river in the River Thames, UK. Our results indicate that there are distinct differences in the bacterial communities between four major habitat types, with contrasting ecological processes shaping their community assembly processes. While the mobile free‐living and particle‐associated communities were consistently less diverse than the fixed sediment and biofilm communities, the latter two communities displayed higher homogeneity across the sampling sites. This indicates that the relative influence of deterministic environmental filtering is elevated in sediment and biofilm communities compared with free‐living and particle‐associated communities, where stochastic processes play a larger role.

Nutrient and microbial water quality of the upper Ganga River, India: identification of pollution sources - Michael J. Bowes; Daniel S. Read; Himanshu Joshi; Rajiv Sinha; Aqib Ansari; Moushumi Hazra; Monica Simon; Rajesh Vishwakarma; Linda K. Armstrong; David J. E. Nicholls; Heather D. Wickham; Jade Ward; et al. (Environmental Monitoring and Assessment, 2020)

Angiosperm symbioses with non‐mycorrhizal fungal partners enhance N acquisition from ancient organic matter in a warming maritime Antarctic - Paul W. Hill; Richard Broughton; Jeremy Bougoure; William Havelange; Kevin K. Newsham; Helen Grant; Daniel V. Murphy; Peta Clode; Soshila Ramayah; Karina A. Marsden; Richard S. Quilliam; Paula Roberts; et al. (Ecology Letters, 2019)
In contrast to the situation in plants inhabiting most of the world’s ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis . Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous d ‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat. Our findings suggest that, in a warming maritime Antarctic, this symbiosis has a key role in accelerating the replacement of formerly dominant moss communities by vascular plants, and in increasing the rate at which ancient carbon stores laid down as moss peat over centuries or millennia are returned to the atmosphere as CO 2 .

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Collision activity during training increases total energy expenditure measured via doubly labelled water - Nessan Costello; Kevin Deighton; Thomas Preston; Jamie Matu; Joshua Rowe; Thomas Sawczuk; Matt Halkier; Dale B. Read; Daniel Weaving; Ben Jones (European Journal of Applied Physiology, 2018)

Impacts of phosphorus concentration and light intensity on river periphyton biomass and community structure - Stephanie J. McCall; Michelle S. Hale; James T. Smith; Daniel S. Read; Michael J. Bowes (Hydrobiologia, 2017)

Legitimacy, access, and the gridlock of tiger conservation: lessons from Melghat and the history of central India - Daniel J. Read (Regional Environmental Change, 2016)

Environmental DNA metabarcoding of lake fish communities reflects long‐term data from established survey methods - Bernd Hänfling; Lori Lawson Handley; Daniel S. Read; Christoph Hahn; Jianlong Li; Paul Nichols; Rosetta C. Blackman; Anna Oliver; Ian J. Winfield (Molecular Ecology, 2016)
Organisms continuously release DNA into their environments via shed cells, excreta, gametes and decaying material. Analysis of this ‘environmental DNA ’ ( eDNA ) is revolutionizing biodiversity monitoring. eDNA outperforms many established survey methods for targeted detection of single species, but few studies have investigated how well eDNA reflects whole communities of organisms in natural environments. We investigated whether eDNA can recover accurate qualitative and quantitative information about fish communities in large lakes, by comparison to the most comprehensive long‐term gill‐net data set available in the UK . Seventy‐eight 2L water samples were collected along depth profile transects, gill‐net sites and from the shoreline in three large, deep lakes (Windermere, Bassenthwaite Lake and Derwent Water) in the English Lake District. Water samples were assayed by eDNA metabarcoding of the mitochondrial 12S and cytochrome b regions. Fourteen of the 16 species historically recorded in Windermere were detected using eDNA , compared to four species in the most recent gill‐net survey, demonstrating eDNA is extremely sensitive for detecting species. A key question for biodiversity monitoring is whether eDNA can accurately estimate abundance. To test this, we used the number of sequence reads per species and the proportion of sampling sites in which a species was detected with eDNA (i.e. site occupancy) as proxies for abundance. eDNA abundance data consistently correlated with rank abundance estimates from established surveys. These results demonstrate that eDNA metabarcoding can describe fish communities in large lakes, both qualitatively and quantitatively, and has great potential as a complementary tool to established monitoring methods.

Soil pH effects on the interactions between dissolved zinc, non-nano- and nano-ZnO with soil bacterial communities - Daniel S. Read; Marianne Matzke; Hyun S. Gweon; Lindsay K. Newbold; Laura Heggelund; Maria Diez Ortiz; Elma Lahive; David Spurgeon; Claus Svendsen (Environmental Science and Pollution Research, 2016)

The effect of anthropogenic arsenic contamination on the earthworm microbiome - Daniel Antony Pass; Andrew John Morgan; Daniel S. Read; Dawn Field; Andrew J. Weightman; Peter Kille (Environmental Microbiology, 2015)
Summary Earthworms are globally distributed and perform essential roles for soil health and microbial structure. We have investigated the effect of an anthropogenic contamination gradient on the bacterial community of the keystone ecological species L umbricus rubellus through utilizing 16 S rRNA pyrosequencing for the first time to establish the microbiome of the host and surrounding soil. The earthworm‐associated microbiome differs from the surrounding environment which appears to be a result of both filtering and stimulation likely linked to the altered environment associated with the gut micro‐habitat (neutral pH , anoxia and increased carbon substrates). We identified a core earthworm community comprising P roteobacteria (∼50%) and A ctinobacteria (∼30%), with lower abundances of B acteroidetes (∼6%) and A cidobacteria (∼3%). In addition to the known earthworm symbiont ( V erminephrobacter sp.), we identified a potential host‐associated G ammaproteobacteria species ( S erratia sp.) that was absent from soil yet observed in most earthworms. Although a distinct bacterial community defines these earthworms, clear family‐ and species‐level modification were observed along an arsenic and iron contamination gradient. Several taxa observed in uncontaminated control microbiomes are suppressed by metal/metalloid field exposure, including eradication of the hereto ubiquitously associated V erminephrobacter symbiont, which raises implications to its functional role in the earthworm microbiome.

Analytical approaches to support current understanding of exposure, uptake and distributions of engineered nanoparticles by aquatic and terrestrial organisms - Carolin Schultz; Kate Powell; Alison Crossley; Kerstin Jurkschat; Peter Kille; A. John Morgan; Daniel Read; William Tyne; Elma Lahive; Claus Svendsen; David J. Spurgeon (Ecotoxicology, 2015)

Including cetaceans in multi-species assessment models using strandings data: why, how and what can we do about it? - Saavedra Camilo; Cabrero Agueda; Cedeira Jose; Cerviño Santiago; Gago Jesus; González-Nuevo Gonzalo; Howell Daniel; López Alfredo; Pierce Graham; Read Fiona; Santos M. Begoña (Frontiers in Marine Science, 2014)

Designing criteria suites to identify discrete and networked sites of high value across manifestations of biodiversity - Eric Gilman; Daniel Dunn; Andrew Read; K. David Hyrenbach; Robin Warner (Biodiversity and Conservation, 2011)

Group structure in a restricted entry system is mediated by both resident and joiner preferences - Lyndon A. Jordan; Carla Avolio; James E. Herbert-Read; Jens Krause; Daniel I. Rubenstein; Ashley J. W. Ward (Behavioral Ecology and Sociobiology, 2010)

Species–soil associations, disturbance, and nutrient cycling in an Australian tropical rainforest - Sean Michael Gleason; Jennifer Read; Adrian Ares; Daniel J. Metcalfe (Oecologia, 2010)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

Cyclone Effects on the Structure and Production of a Tropical Upland Rainforest: Implications for Life-History Tradeoffs - Sean M. Gleason; Laura J. Williams; Jennifer Read; Daniel J. Metcalfe; Patrick J. Baker (Ecosystems, 2008)

Rapid high-resolution MHC class I genotyping of Chinese rhesus macaques by capillary reference strand-mediated conformational analysis - Alex J. Blasky; Julie A. Karl; Roger W. Wiseman; Daniel S. Read; David H. O’Connor (Immunogenetics, 2008)

Identification of MHC class I sequences in Chinese-origin rhesus macaques - Julie A. Karl; Roger W. Wiseman; Kevin J. Campbell; Alex J. Blasky; Austin L. Hughes; Betsy Ferguson; Daniel S. Read; David H. O’Connor (Immunogenetics, 2008)

Assessing aquifer susceptibility to and severity of atrazine contamination at a field site in south-central Wisconsin, USA - Jonathan Levy; Gordon Chesters; Daniel P. Gustafson; Harry W. Read (Hydrogeology Journal, 1998)